Global research progress on obstructive sleep apnea in the field of radiological imaging: bibliometric and visualization analysis - Zhang, Yi; Chai, Xiaoyuan; Sun, Peng; Li, Xiangsheng (Frontiers in Neurology, 2025)
BackgroundThis study aims to assess the intersection of OSA with radiological imaging through bibliometric analysis, exploring research trends and emerging hotspots to identify future research directions.MethodsThis study conducted a literature search for publications related to OSA and radiological imaging from 2004 to 2023 in the Web of Science database. We utilized tools such as CiteSpace, R language, and VOSviewer for bibliometric analysis to explore key trends and hotspots in this interdisciplinary field.ResultsThe search yielded 2,000 publications, showing a fluctuating upward trend in publication volume. Research predominantly originates from countries/regions such as the United States, China, and Turkey. Leading journals in this field include Sleep, the American Journal of Respiratory and Critical Care Medicine, and Chest; with 7,202 research institutions involved, notable ones include the University of California system, Harvard University, the University System of Ohio, Capital Medical University, and Seoul National University. A total of 10,099 researchers have contributed to this field, including prominent figures such as Kumar R, Harper RM, and Schwab RJ. Keyword analysis indicates current research hotspots are imaging diagnostic techniques for OSAHS, comorbidities associated with OSAHS, and the pathogenesis of OSAHS-related comorbidities.ConclusionCurrently, imaging studies on OSAHS are increasingly becoming a focal area, and new imaging diagnostic techniques for OSAHS require further validation through studies with larger sample sizes and more standardized methods. Additionally, research into the interactions between OSAHS and its comorbidities, different pathogenic mechanisms, and the integration of neuroimaging biomarkers with negative cognitive outcomes urgently needs to be deepened.